The Effect of Customer Relationship Management (CRM) on Customer Loyalty and Customer Satisfaction at Saung Rindu Alam Restaurants In Gowa District South Sulawesi - Nurul Athirah Imran (Scientium Management Review, 2022)
One good strategy to retain customers is Customer Relationship Management (CRM). CRM focuses more on what customers value, not on the products the company wants to sell. Through the implementation of CRM, companies are expected to be able to build good communication and relationships with their customers. Consumer satisfaction is an important factor in creating loyalty, by feeling satisfied with a product, consumers will automatically return to buy and consume the product. In the end, this is expected to be the main driver for achieving the company's own profits, where when consumers are loyal to a product, of course it will encourage continuous product sales because the biggest profits are obtained by the company from loyal customers. Therefore, this study aims to determine the effect of Customer Relationship Management (CRM) on customer loyalty and customer satisfaction at saung rindu alam restaurants in Gowa District, South Sulawesi. This research is quantitative and the data collection method uses a questionnaire of 105 samples. Methods of analysis using validity, reliability, path analysis, and hypothesis testing. The results showed that customer relationship management has an effect on customer loyalty, customer relationship management has an effect on customer satisfaction, customer satisfaction has an effect on customer loyalty, and there is an indirect effect on customer relationship management on customer satisfaction as an intervening variable.